Impact of the Effective Exchange Rate on the Trade Balance of Sri Lanka: Evidence from 2000 to 2013. (May 2015) - Senadheera, Yashodha Warunie
This study investigates the possibility of improving the trade balance of Sri Lanka through currency depreciation. An error correction model (ECM) was used to examine the short-term and long-term effects of nominal and real effective exchange rate depreciation on the trade balance. While there is no long-run relationship between the real effective exchange rate and the trade balance, depreciation of the nominal effective exchange rate will lead to a deterioration of the trade balance in the long term. Further, the results indicate that there is a positive causality relationship from the real GDP to the trade balance. Conversely, growth in money supply will worsen the country's trade balance in the long run. The empirical findings show that currency devaluation is not an effective policy tool to improve the country's trade balance. JEL Classification: F 140